2013
DOI: 10.2147/tcrm.s29179
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and management of miliary tuberculosis: current state and future perspectives

Abstract: Tuberculosis (TB) remains one of the most important causes of death from an infectious disease, and it poses formidable challenges to global health at the public health, scientific, and political level. Miliary TB is a potentially fatal form of TB that results from massive lymphohematogenous dissemination of Mycobacterium tuberculosis bacilli. The epidemiology of miliary TB has been altered by the emergence of the human immunodeficiency virus (HIV) infection and widespread use of immunosuppressive drugs. Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 101 publications
3
80
0
9
Order By: Relevance
“…Hypercalcemia has been described in 13.4% of the patients with disseminated TB, [2] in our study it was found only in 1/100 (1%) patient. In our series tuberculin skin tests were positive in 42% of the cases, which falls within the range of 20-70% mentioned in the literature [14]. Skin testing is frequently unreliable and of no help in excluding or confirming the disease.…”
Section: Investigations and Proceduressupporting
confidence: 80%
See 4 more Smart Citations
“…Hypercalcemia has been described in 13.4% of the patients with disseminated TB, [2] in our study it was found only in 1/100 (1%) patient. In our series tuberculin skin tests were positive in 42% of the cases, which falls within the range of 20-70% mentioned in the literature [14]. Skin testing is frequently unreliable and of no help in excluding or confirming the disease.…”
Section: Investigations and Proceduressupporting
confidence: 80%
“…Meningitis was found in 23 (23%) of our patients, which falls within the range of 10-30% mentioned in the literature [3,13,14]. Choroidal tubercles are pathognomonic of disseminated TB and offer a valuable clue to the diagnosis [14,15]. In our patients, there was no mention of the frequency of choroidal tubercles since funduscopic examinations were not routinely performed.…”
Section: Clinical Featuressupporting
confidence: 63%
See 3 more Smart Citations